Intermediate economics for West Africa - Anderson, David (London : Macmillan, 1980)
Written to meet the needs of those students who have progressed beyond ordinary level economics, and are studying for the more advanced level examinations.
Includes index.
oif 09/02/816
Loans
Keywords: Economics; Africa, West